Pembelajaran PPKn sebagai Sarana Menanamkan Semangat Persatuan dan Kesatuan pada Siswa SD - Andini Agustya Utami; Amelia Putri; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the effectiveness of Civic and Pancasila Education (PPKn) in instilling the spirit of unity and integrity among elementary school (SD) students. Using a qualitative approach through a literature review method, this research examines various scholarly works and relevant studies to develop effective and contextual PPKn learning strategies. The findings reveal that PPKn plays a strategic role in shaping national character through the understanding of national values, legal norms, and national identity. Programs such as “Sahabat Pancasila” serve as successful examples of implementing unity values in real school settings. However, challenges remain, such as the lack of variety in teaching methods and the low level of students' affective engagement. Therefore, recommended strategies include value-based learning models, contextual approaches, and regular teacher training. This research is expected to contribute to the development of character education policies and strengthen the role of PPKn in nurturing a young generation that is patriotic and tolerant.